The Influence of Subak Farmer Groups on Weir Intake Operations - Ida Bagus Gede Indrayana; Luh Ayu Putri Wedayanti Pulasari; I Wayan Shanjaya Dharmaputra (Universitas Pendidikan Nasional, 2026)
Subak is a traditional irrigation management system in Bali that integrates social, religious, and technical dimensions within agricultural practice through collective agreements among farmers. This study examines the influence of Nabdab Yeh, the water allocation mechanism employed by the Subak institution on the intake operation of Mambal Weir, which supplies irrigation water to 43 Subak units within the Tukad Ayung Irrigation Area. Quantification Analysis I was applied to assess the impact of four principal determinants, namely antecedent precipitation, ponding depth, water demand, and Paddy cultivation percentage. Each determinant was systematically categorized and converted into binary variables to formulate a predictive model. The resulting model yielded an R-total value of 0.78, indicating a strong correlation and high predictive accuracy. Partial correlation analysis revealed that antecedent precipitation (R-partial = 0.515) exerted the most dominant influence, followed by ponding depth (0.470), while water demand (0.249) and Paddy percentage (0.220) demonstrated comparatively lower significance. These findings affirm that climatic and hydrological conditions constitute the primary determinants governing intake operations, whereas agricultural cropping patterns function as an adaptive response to prevailing water availability. The developed model provides a scientific basis for adaptive irrigation management while sustaining the local ecological wisdom inherent to the Subak system.